Translating isolated sentences in a foreign language class: Why not? - Welker, Herbert Andreas (2003)
In recent years various authors have defended the reintroduction of translation into foreign language teaching. Generally they propose the use of texts whose context is known and which are authentic. In this article I argue that in the initial stages it makes sense to have the learners translate isolated sentences and non-authentic texts.